Roots - Haley, Alex (Vintage Random House, 1977)
About the author (2018) Alex Haley was born in Ithaca, New York in 1921. After his retirement from the Coast Guard in 1959, Haley began his writing career and eventually became a senior editor for Reader's Digest. Haley conducted the first Playboy Interview for Playboy magazine. The interview, with jazz legend Miles Davis, appeared in the September 1962 issue. One of Haley's most famous interviews was a 1963 interview with Malcolm X for Playboy, which led to collaboration on the activist's autobiography. Haley later ghostwrote The Autobiography of Malcolm X, based on interviews conducted shortly before Malcolm's death. The book was published in 1965 and was a huge success, later named by Time magazine one of the ten most important nonfiction books of the twentieth century. In 1976 Haley published Roots- The Saga of an American Family, a novel based loosely on his family's history. Haley traced in it his ancestry back to Africa and covered seven American generations, starting from his ancestor, Kunta Kinte. Roots were eventually published in thirty-seven languages, won the Pulitzer Prize, and went on to become a popular television miniseries in 1977, as well as causing a renewed interest in genealogy.